2015
DOI: 10.1590/1677-3225v14n3a11
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of a flowable composite light-activated through ceramics of different shades and thicknesses

Abstract: The cementation of thin ceramic veneers employing fluid light-activated resin-based materials is a common procedure in the dental practice. Aim: To evaluate the influence of ceramic thickness and shade on the degree of conversion (DC) of a flowable light-activated material. Methods: flowable resin composite (Tetric N-Flow -shade A1) was light-activated through ceramic discs of two shades (IPS Classic -A1 and A3) in three thicknesses (0.5, 0.7 and 1.0 mm). For control, the resin composite was light-activated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Some studies found that thickness and translucency were not a major factor in the extent of polymerization of the resin cement. However, these studies examined specimens that were relatively thin (1.5 mm or less) and hence the effects of the differing translucencies may not have been as significant [29,30]. Others had other issues with not ensuring that the curing light was calibrated as the output of light can deteriorate over time [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that thickness and translucency were not a major factor in the extent of polymerization of the resin cement. However, these studies examined specimens that were relatively thin (1.5 mm or less) and hence the effects of the differing translucencies may not have been as significant [29,30]. Others had other issues with not ensuring that the curing light was calibrated as the output of light can deteriorate over time [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type, thickness, and color of the ceramic, the radiant exposure may not be enough due to attenuation, compromising the polymerization process. [ 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dentists who wish to avoid the heating procedure can use high-filled flowable resin composites for bonding purposes (Furuse at al., 2015 , Mutlu et al., 2021 ). However, it is important to note that there is currently a lack of investigation regarding these specific luting procedures for indirect ceramic and composite restorations.…”
Section: Introductionmentioning
confidence: 99%